Menyibak Sistem Fonetik Bahasa Indonesia dan Bahasa Arab serta Implikasinya dalam Pembelajaran BIPA - Salis Hilda Yoviyani; Yeti Mulyati (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2023)
Realizing Indonesian as an international language can be done by teaching Indonesian to Foreign Speakers (BIPA), but in the BIPA learning process we often face problems, especially in terms of phonology. Arabic speakers often find it difficult to pronounce sounds in Indonesian. Therefore, this research was conducted to analyze the differences and similarities between the pronunciations of the two languages using a qualitative descriptive approach and a contrastive analysis. In the results of the study, several similarities and differences were found between the pronunciation of Indonesian and Arabic. With similarities, it will make it easier for Arabic learners to learn Indonesian sounds. However, the existence of differences will also cause learning difficulties and require more attention to some aspects. Therefore, the results of this study can assist BIPA teachers in determining teaching materials, learning models, teaching units, and syllabus that are right on target through consideration of contrastive analysis.